The first eyeless species of Tomocerus from China (Collembola, Tomoceridae) with notes on genera Tomocerus and Pogonognathellus - Yu, Daoyuan; Deharveng, Louis (Zootaxa, 2015)
A new cave tomocerid from Guangxi Zhuang Autonomous Region, South China is described. Tomocerus caecus sp. nov. is characterized by the absence of ocelli, the absence of posterior macrochaetae on head and the reduced number of teeth on unguis and mucro. The generic position of the new species is discussed. Tomocerus caecus sp. nov. is similar to the East Asian species Tomocerus kinoshitai Yosii, 1954 and Tomocerus similis Chen & Ma, 1997 mainly in the shape of dental spines and the small number of teeth on unguis and mucro, but different from the latters in the absence of ocelli and pigment. The differences between the genera Tomocerus Nicolet, 1842 and Pogonognathellus (Börner, 1908) are discussed with a special focus on the work of Massoud & Ellis (1974) that was long ignored by collembologists.